EFFECT OF VIBRATION AND HEAT COMBINATION ON PRIMARY DYSMENORRHEA - Hoseini, Mansoureh; Gharahtapeh, Sheida Rafiezadeh; Jahazi, Azam (BALI MEDICAL JOURNAL; Vol 4 No 1 (2015), 2015)
Background: Primary dysmenorrhoea is a common, idiopathic, chronic pelvic pain syndrome, with unknown aetiology which ? about 50% of women with regular menstrual period suffer. This study was designed to determine the effect of vibration and heat on primary dysmenorrhea. Materials and Methods: In this clinical trial, 75 female students aged 18 22 years old were evaluated for two menstrual cycles. At the first cycle the participants received the routine pain-relief method (synthetic or herbal medicine and traditional remedies). At the second cycle for each participant combined vibration-heat device was applied for ten minutes during ? menstrual pain. The average of perceived leg pain, lumbar pain and abdominal pain scores at two cycles were determined. The data were analyzed based on Wilcoxon and T tests by using SPSS (v 16.0) for Windows. Results: The average of all perceived pain scores at two cycles were significantly different before pain relief and after both routine methods and using the device (p<0.001). Those were more significantly reduced after using the device in comparison of using routine methods (p<0.001). Conclusion: Since ?vibration-heat? is an effective pain relief method, it can be used as a complementary alternative medicine in primary dysmenorrhea reduction.
Keywords: Vibration, Heat, Dysmenorrhea, vibration.